A comparative assessment of treatment results of oblique and spiral fractures of the shin bones with use of Ilizarov’s apparatuses and external fixation rod devices - Rokutov, Victor (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2011)
Results of treatment of 67 patients with oblique and spiral fractures of their tibia in its lower one-third part were comparatively analysed. In the first group, which consisted of 45 patients, Ilizarov’s apparatuses were used. The second group (22 cases) was treated with external fixation rod devices. The obtained results were assessed according to the following indices: duration of the operation, efficacy of reposition, functional activity of patients, presence of inflammatory processes, scope of movements in adjacent joints, terms of fixing in the apparatus and radiometric parameters. The above analysis revealed great advantages of rod devices over Ilizarov’s apparatuses in patients with oblique and spiral tibial fractures.